Breaking Ground: Improving Undergraduate Engineering Projects through Flipped Teaching of Literature Search Techniques. - Tasha Maddison; Donna Beneteau; Brandy Sokoloski (Issues in Science and Technology Librarianship, 2014)
This case study describes the use of flipped teaching for information literacy instruction in a new course, Drill, Blast, and Excavate GeoE 49: within the mining option for geological engineering (GeoE) students. These students will enter the mining industry with less discipline-specific knowledge than a student that graduated with a degree in mining engineering, yet on-the-job training provided by the employer will fill in most of the technical gaps. Engineers in the workplace can connect to information sources online and do not need to rely solely on co-workers, short courses, and conferences for upgrading their knowledge. With this in mind, we developed a flipped teaching assignment to teach students how to effectively and efficiently access electronic information on topics faced by geological engineers in the field. The course included a research project that allowed the students to practice these information retrieval and evaluation techniques so as to better prepare them for the working world. Student feedback revealed a high level of engagement in the discovery of these research strategies and the instructor noted that these techniques were applied successfully in the students written reports and oral presentations. [ABSTRACT FROM AUTHOR]